2013
DOI: 10.1089/jwh.2012.3998
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Potential Health Disparities in Excessive Gestational Weight Gain

Abstract: Introduction: Although previous public health efforts have focused on redressing health disparities associated with insufficient gestational weight gain, examination of the impact of excessive gestational weight gain is warranted currently given the 2009 revision of the Institute of Medicine (IOM) gestational weight gain guidelines for obese women coupled with rising rates of obesity, particularly among African American women. Materials and Methods: In the years [2004][2005][2006][2007][2008] 4619 African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 39 publications
4
45
0
3
Order By: Relevance
“…17 Although minority women are more likely to enter a pregnancy as overweight or obese compared to whites, in general, Hispanic and black women are more likely to have inadequate GWG and less likely to have excessive GWG compared to whites. 1820 For example, in a study of birth records from 2007–2010 in Colorado, Hispanic and black women had an increased odds for inadequate GWG (aOR 1.08, 95% CI 1.04–1.11; aOR 1.12, 95% CI 1.06–1.19, respectively) and decreased odds for excessive GWG (aOR 0.84, 95% CI 0.81–0.86; aOR 0.96, 95% CI 0.90–1.00, respectively) compared to non-Hispanic whites. 21 Deputy et al also examined racial-ethnic associations with GWG, but noted that the odds varied by BMI.…”
Section: Epidemiology and Trends In Gestational Weight Gain In The Unmentioning
confidence: 99%
“…17 Although minority women are more likely to enter a pregnancy as overweight or obese compared to whites, in general, Hispanic and black women are more likely to have inadequate GWG and less likely to have excessive GWG compared to whites. 1820 For example, in a study of birth records from 2007–2010 in Colorado, Hispanic and black women had an increased odds for inadequate GWG (aOR 1.08, 95% CI 1.04–1.11; aOR 1.12, 95% CI 1.06–1.19, respectively) and decreased odds for excessive GWG (aOR 0.84, 95% CI 0.81–0.86; aOR 0.96, 95% CI 0.90–1.00, respectively) compared to non-Hispanic whites. 21 Deputy et al also examined racial-ethnic associations with GWG, but noted that the odds varied by BMI.…”
Section: Epidemiology and Trends In Gestational Weight Gain In The Unmentioning
confidence: 99%
“…(10) However, up to 83% of obese pregnant women exceed these recommendations. (11-13) Given that most women are motivated to have “healthy pregnancies,” gestational weight gain (GWG) is potentially modifiable through behavioral interventions that target physical activity, nutrition, etc. Accordingly, the IOM report stated that interventions will be needed to assist obese women to meet the GWG goals.…”
Section: Introductionmentioning
confidence: 99%
“…This finding, however, is consistent with an existing study, which found that African Americans and Hispanics were less likely than Caucasian women to exceed the IOM guidelines. 2 Their study did not, however, examine risk factors for insufficient weight gain. There may be a subpopulation of women who have trouble gaining weight during pregnancy due to food insecurity or competing life demands.…”
mentioning
confidence: 99%
“…1 To date, a few studies have reported the prevalence of adequate gestational weight gain using the 2009 IOM recommendations. [2][3][4] Similarly, only a few studies have been conducted to assess whether current prenatal care programs effectively promote adequate weight gain during pregnancy. 2 Prenatal care can help prevent potential health problems during the course of pregnancy through screening and the recommendation of healthy lifestyle changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation